Comparative Analysis of Kazakhstan and China: By Human Capital and Competitiveness - Kaster Sarkytkan (Journal of Central Asian Studies, 2024)
The article aims to assess the importance of education and science in the development of the national economy and geopolitical potential through a comparative analysis of the Republic of Kazakhstan and the People's Republic of China in terms of human capital and competitiveness. To achieve this goal, the following tasks are defined: the geographical location, the natural resource potential of the two states, features of the transition to the market, and the importance of human capital in the development of the national economy. To reveal the tasks set, the methods of historical, narrative, geographical modeling, and statistical, comparative analysis were used. The results of the research showed that independence is a key factor in the development of the domestic economy, but human capital and competitiveness are the most important driving forces in the development of the national economy. The author compares the economic and geographical positions of Kazakhstan and China, using the countries with the most national wealth and high competitiveness in the world as an example. The authors conclude that the main reason for the divergence in the level of economic development of the two countries is that China paid maximum attention to science and education after the transition to a market economy and achieved results. In addition, Kazakhstan's identified priorities and growing financial situation in the fields of education and science will be announced in the future. A clear example shows that high competitiveness also affects foreign trade and investment.